Altered mitochondrial mass and low mitochondrial membrane potential of immune cells in patients with HBV infection and correlation with liver inflammation - Ma, Liling; Han, Qingzhen; Cheng, Longji; Song, Huafeng; Qiang, Rui; Xu, Ping; Gao, Fei; Zhu, Li; Xu, Junchi (Frontiers in Immunology, 2024)
IntroductionMitochondrial membrane potential (MMP) and mitochondrial mass (MM) affect mitochondrial function and lymphocyte activation, but few studies on HBV infection exist. This study aimed to investigate the regulatory mechanism of mitochondrial dysfunction during HBV infection and its clinical significance by analyzing the alterations of MM and MMPlow in peripheral blood immune cells.MethodsThe study enrolled 90 participants, including healthy volunteers(HC) and patients with HBV infection, HBV patients were divided into chronic hepatitis B patients (CHB) and liver cirrhosis (LC) according to the study, and CHB was also divided into an inflammation group and a non-inflammation group. Flow cytometry was used to analyze the changes of MM and MMPlow in peripheral blood immune cells. These analyses were correlated with the presence of CHB and LC and indexes related to liver inflammation.ResultsThe study revealed significant variations in the percentage of MMPlow and MM of CD8+T cells associated with the progression of the disease. The MMPlow percentage of CD8+T cells in the LC group exhibited a notable decrease compared to the HC group and CHB groups. Moreover, MMPlow of CD8+T cells demonstrated potential in distinguishing CHB and LC (AUC=0.7341, P=0.0032). Furthermore, in exploring the link between mitochondrial function of immune cells and liver inflammation, the study found a negative correlation between the MMPlow ratio of CD4+T and CD8+T cells and AST (p=0.0039 and P=0.0070, r=-0.4405 and r=-0.4146), while the MM of CD8+T cells displayed a positive correlation with AST (p=0.0013, r=0.4865). In CHB patients with normal ALT but liver inflammation detected on B-scan ultrasonography, a significant decrease was observed in the MMPlow percentage of CD8+T (66.13 ± 14.27), CD56+NK(57.77 ± 17.40) and CD4-CD8-T (61.98 ± 15.98) cells. Furthermore, it was also found that the percentage of MMPlow in CD4-CD8-T cells could serve as an indicator for early liver inflammation and injury (AUC=0.8408, P=0.0052).DiscussionIn this study, we conducted a systematic analysis of the percentage of lymphocyte MMPlow and MM in various stages of HBV infection. Our findings revealed a correlation between MMPlow and MM and early liver inflammation, as well as the progression of the infection. This study marked the first demonstration of the clinical diagnostic value of MMPlow and MM in HBV infection. Furthermore, this was the first study to discuss the mitochondria of lymphocytes and liver inflammation in HBV infection. It enhanced the understanding of the role of T cells in liver inflammation, and elucidated potential markers for the early detection of liver injury and clinical cirrhosis.